THE ROLE OF FOOD MANUFACTURING INDUSTRIES IN SHAPING INDONESIA’S NATIONAL FOOD SECURITY POLICY FRAMEWORK - Poppy S. Nurisnaeny; Djoko Andoko; Saparuddin Saparuddin (RADJA PUBLIKA, 2025)
This study aims to examine the strategic role of the food processing industry in forming a national food security policy framework in Indonesia. In the context of increasingly complex global dynamics and domestic challenges, the food processing sector is one of the key elements in supporting the availability, affordability, and sustainability of food. This study uses a literature review method by examining various scientific sources, government policies, and secondary data related to industry performance and national food policies. The results of the study show that the food processing industry not only plays a role in increasing the added value of agricultural products, but also in creating an efficient distribution system, expanding market access, and strengthening strategic food reserves. Furthermore, this industry has a significant contribution to the formation of policies that are responsive to the food crisis, increasing nutritional security, and achieving sustainable development goals. Thus, close integration between the industrial sector and public policy is an important prerequisite for strengthening national food security in the future.